Information sources of Kazakh encyclopedic publications - Ozbekova, Г.; Ertasova, Г.; Alim, Ә. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2022)
In the article investigated sources Kazakh encyclopaedic edition in connection with history of the Kazakh people. Древнетюркские писменные monuments - «Тонукук», «Бильге Каган» and encyclopaedic work of medieval scientists - Ибн Сины and Аль-Фараби is analysed as basis of Kazakh certificate editions. Encyclopaedic features work of Ж.Баласагун, М.Кашкари similarly is research basis.